Pengaruh mutu terhadap kepuasan pasien pada pelayanan rawat jalan RSUD Prof. Dr. W.Z. Johannes Kupang - Buky, Hendrosius Endo; Pandie, David B. W.; Littik, Serlie K. A. (Journal of Evidence-based Nursing and Public Health, 2024)
The quality of health services is the perfection of health services in meeting patient needs and demands; the better the quality of service, the more it will influence patient satisfaction. Survey results show that there are still many patients who are dissatisfied with hospital services. This study aims to determine the partial effect of quality from five qualities on patient satisfaction in outpatient services at RSUD, Prof. Dr. W.Z. Johannes Kupang. The research method is quantitative research with a descriptive approach, with the population in this study including all patients visiting the outpatient clinic at Prof. Hospital. Dr. W.Z. Johannes Kupang. The sampling technique used in this research is simple random sampling. The data in this study was taken using a questionnaire distributed to polyclinic outpatient patients at Prof. Hospital. Dr. W.Z. Johannes Kupang was numbered 94. The data was analysed using the multiple linear regression test, showing that the responsiveness and empathy variables had a significant effect on the reliability of patient satisfaction with a sig value. p = 0.00 and p = 0.021 (p<0.05), while the variables tangle (0.398), reliability (0.893), and assurance (0.822) are not significantly related to patient satisfaction because the p value is> 0.05. So it is necessary to improve the quality of hospital services for better service.